Markets in catholic social teaching - Rogowski, Robert (Managerial Economics, 2016)
An aim of this article is to present the Catholic social teaching in regard to one basic institutions of economic life that is the market. The analysis starting point is an Encyclical of Pope Leo XIII, Rerum novarum, who initiated Catholic social teaching. All the social encyclicals were studied, which directly or indirectly refer to the market category. In the final part of the article, a synthesis of teaching the Catholic Church in market terms was carried out.